TERAPI BERMAIN BAGI SISWA KORBAN BENCANA TSUNAMI DI KECAMATAN SUMUR BANTEN - Evi Afiati; Alfiandy Warih Handoyo; Siti Muhibah; Ibrahim Al Hakim (Universitas Sultan Ageng Tirtayasa, 2020)
One year after the Tsunami Selat Sunda disaster, there were still victims who were traumatized. This study aims to describe the implementation of play therapy for students affected by the Sunda Strait Tsunami disaster. This research method is descriptive, that will dscribe how to do play therapy for traumatized students. Based on the results of the assessment, it is known that there are still students who experience physical, emotional, and habitual disorders. Play therapy activities carried out in three stages, namely initiation, outdoor activities, and indoor activities. The final results show that after participating in play therapy activities students begin to feel more comfortable because they can pour out their fears. Students also begin to reduce anxiety and fear.